gg -> h -> tau(+)tau(-) at the upgraded Fermilab Tevatron - Belyaev, A. (2003)
We study the neutral Higgs boson production via the gluon fusion process with the tau(+)tau(-) final state at the upgraded Fermilab Tevatron, including a complete simulation of signal channels and leading background processes. For the SM Higgs boson, this h --> tau(+)tau(-) channel may provide important addition for the Higgs boson discovery in the mass range 120 - 140 GeV. In minimal supersymmetric models, natural enhancement for the signal rate over the SM expectation makes the h, H, A --> tau(+)tau(-) signal observable for large tan beta and low MA, which may lead to full coverage for SUSY Higgs parameters at the Tevatron with a moderate integrated luminosity.